Wykorzystanie portalu Twitter jako narzędzia w zarządzaniu problemowym (issue management) w obszarze polityki - Drosik, Adam (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
There is no denying that one of the foundations of contemporary politics, and perhaps the most important, is the image. The image of politician and the party, the image which is so carefully looked after by numerous specialists. Elaborately prepared design, which is delicately managed to create the right impression. At the same time this construction is exposed to dozens of hazards that can cause all sorts of crisis situations. So far, in the practice of public relations there is a belief that a crisis in any organization (entity) is inevitable, like death and taxes. The department of public relations is also responsible for crisis management during the course of events of the crisis situation. However, today more and more often, we go one step further, pointing out that it is necessary to strive for a situation in which any possible crisis will be detected early or even beforehand, and thus the appearance of the crisis situation will be postponed into the indefinite future. For anticipating the crisis, from the point of view of public relations, responsible is “issue management” and the purpose of this article is to present to use of the Twitter portal as a tool used to foresee a crisis situation with regard to the political image. The example of actions taken by the Ministry of Regional Development during a press conference of Law and Justice party in November 2013 was used as a case study.
Twitter as a tool in issue management in the area of policy
Keywords: crisis; crisis management; issue management; social media